Restriction of the Rights of Russian Senators as a Political Responsibility - Garipov, Ruslan Faritovich; Igonin, Denis Ivanovich (Cuestiones Políticas, 2020)
This article explores the features of the implementation of individual parliamentary rights by members of the Federation Council, the upper house of the Russian legislative assembly. The relevance of the study is since in recent years there has been a transformation in informal practices of political influence on parliamentarians. In this sense, the object of the study was the analysis of individual legal norms, the regulations of the Federation Council and the practice of holding parliamentary hearings. The authors focused on the negative consequences expressing the responsibility of senators, considering the ambiguous statutory regulation of such measures in modern Russian politics. During the development of the scope of activities carried out by the upper house of the Federal Assembly, the reasons by which its members could lose their powers were significantly expanded. By way of conclusion, it was noted that, despite the rarity of the application of such sanctions, the authors recorded a systematization of forms and measures of responsibility used for political purposes. Such tendencies create artificial barriers to the implementation of certain senatorial powers and acquire a political character.